mRNA mistranslation in Saccharomyces cerevisiae - Paulo, Jorge Fernando Ferreira de Sousa (2018)
The genetic code is defined as a series of biochemical reactions that establish the cellular rules that translate DNA into protein information. It was established more than 3.5 billion years ago and it is one of the most conserved features of life. Over the years, several alterations to the standard genetic code and codon ambiguities have been discovered in both prokaryotes and eukaryotes, suggesting that the genetic code is flexible. However, the molecular mechanisms of evolution of the standard genetic code and the cellular role(s) of codon ambiguity are not understood. In this thesis we have engineered codon ambiguity in the eukaryotic model Sacharomyces cerevisiae to clarify its cellular consequences. As expected, such ambiguity had a strong negative impact on growth rate, viability and protein aggregation, indicating that it affects fitness negatively. However, it also created important selective advantages in certain environmental conditions, suggesting that it has the capacity to increase adaptation potential under environmental variable conditions. The overall negative impact of genetic code ambiguity on protein aggregation and cell viability, suggest that codon ambiguity may have catastrophic consequences in multicellular organisms. In particular in tissues with low cell turnover rate, namely in the brain. This hypothesis is supported by the recent discovery of a mutation in the mouse alanyl-tRNA synthetase which creates ambiguity at alanine codons and results in rapid loss of Purking neurons, neurodegeneration and premature death. Therefore, genetic code ambiguity can have both, negative or positive outcomes, depending on cell type and environmental conditions.